RELATIONSHIP BETWEEN WORK STRESS AND PERFOMANCE OF EMPLOYEES: A CASE STUDY OF TRANSIT HOTEL IN NAIROBI CITY COUNTY - Kinyita, Pauline (Archives of Business Research, 2015)
Employees are the most important asset of any organizations and need to be guarded against factors that can hinder their performance at work. This is primarily the responsibility of the management in any organization, however; some managers ignore this issue and label it as unimportant, as a result employees in the hotel sector of Nairobi are increasingly exhibiting high levels of work stress and this has in turn affected their overall performance at work. The aim of this study is to determine the relationship that exists between work stress and performance of employees in the hotel sector in Nairobi. It also aimed to identify the various sources of stress and their effect on employee performance and to investigate the techniques employed by managers of these organizations to help the employees cope with work stress. The study was conducted in Transit Hotel in Ngara Nairobi City, County. It focused on a target population of 5 managerial and 55 non management staff. The research used descriptive research design and employed simple random sampling and stratified random sampling as the data collection techniques, resulting in a sample of 31 respondents. The data collection tool used was a questionnaire. Descriptive statistics using frequency tables was used to analyse the data while Chi square was used to analyse the inferential statistics. The findings showed a relationship between work stress and employee performance and that work stress significantly affects the performance of an individual and stress management techniques are not highly regarded or utilised by management.